ANALISIS TINGKAT PEMAHAMAN KOMPUTER AKUNTANSI (STUDI EMPIRIS PADA MAHASISWA AKUNTANSI DI PENDIDIKAN EKONOMI FKIP UR) - Johan, Rina Selva; ', Mentari; ', RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Some students from High School and from Non AccountancyVocational Schools face difficulties on understanding accountancy computer subject(MYOB Accounting). Students graduated from Accountancy Vocational are easier tounderstand the subject because they had learned it before entering the universitycompare by the students graduated from High Schools or Non Accountancy VocationalSchools. The aim of this research is to test the ability of understanding of usingcomputer in accountancy on students gradueted from Non Accountancy VocationalSchools and Science And Social department in High Schools. This research isconducted in Teacher Training and Educational Faculty, Economic Department, RiauUniversity. The result shows that there is a difference on understanding theaccountancy computer subject (MYOB Accounting) on Non Accountancy VocationalSchools and Social department in High Schools. While Science department in HighSchools are not defined in this researchKeywords: Comprehension, Accountancy Computer